An imaginative geography of linear gender: Bathrooms, locker rooms and cis vulnerability. Issue 1 (1st March 2023) - Vähäpassi, Valo
The wave of anti-trans bathroom bills since 2015 has raised awareness of the importance of bathroom politics for trans people. Long before this, feminist scholars have argued that bodies and spaces are simultaneously forced into a gender binary through the regulation of gender-segregated spaces such as bathrooms. In this article, I offer a trans feminist reading of the media events and rhetoric of the Christian right opposing trans access. I analyse the opposition of the Christian right towards trans access to gender-segregated spaces as an imaginative geography of linear gender. As I argue, the Christian right builds an imaginative geography of a threatened, White 'cis America' through rhetorical devices. Vulnerability attached with micro-level spaces across the United States is evoked through the figure of the child, 'women and children' and the predator. Through these rhetorical devices, bodies and spaces are imagined simultaneously. These figures work as powerful 'stopping devices' for anyone bending the straight line of linear gender. These stopping devices can mobilize cis bodies around a defence of a conservative gender order, legitimize a 'protective' control over cis girls and women, make living in the social world even harder for trans people, all the while envisioning an exclusionary 'America'.